Paradigmatic-Syntagmatic Structure Relation in the Narrative of Animated Music Video “Sabda Alam” as a Campaign Design for Endemic Birds in Indonesia - Wardani, Winny Gunarti Widya; Syahid, Syahid; Akbar, Taufiq (VCD, 2024)
There are many media campaign models, one of which is an animated music video. In 2021, an animated music video entitled “Sabda Alam” by students of SMK Raden Umar Said (RUS) Kudus won appreciation from national and international filmmakers at the Balinale International Film Festival 2021. As an audio visual-based campaign design, “Sabda Alam” has become one of the creative economic product models produced by vocational high school students. This video presents a narrative about the life of endemic birds in Indonesia that are threatened with extinction. The urgency of the issue of endangered species underlies the importance of this study to analyze the structure of visual narratives in animated music video designs that is able to carry campaign messages in ways that attract attention. This research uses a combination method, namely qualitative and quantitative analysis using a paradigmatic and syntagmatic structural approach in semiotic theory. Qualitatively, examines the visual narrative of animated music videos based on three storyline structures, namely the beginning, middle, and ending storyline. In each part of the storyline, analysis refers to the visualization of visual signs of the subject, event, and setting in the scene. While quantitatively, this study formulates the audience’s level of understanding of the campaign message in the animated music video. The results of the analysis of the structure of the visual narrative show that there are paradigmatic associations from the scenes that link the existence of interest as a message clue. While syntagmatically, analysis refers to the existence of a function in the scene about something. The two are interrelated to produce a campaign message about the importance of protecting endemic birds in Indonesia. This study can be an academic reference, both in vocational high schools and universities, in developing inspiring campaign media designs in the creative industry.